More Dispersion, Higher Bonuses? On Differentiation in Subjective Performance Evaluations - Kampkötter, Patrick; Sliwka, Dirk (Journal of Labor Economics, 2018)
We investigate the claim that supervisors do not differentiate enough between high- and low-performing employees when evaluating performance. In a first step, this claim is illustrated in a formal model showing that rating compression reduces performance and subsequent bonus payments. The effect depends on the precision of performance information and may be reversed when cooperation is important. We then investigate panel data spanning different banks and find that stronger differentiation indeed increases subsequent bonus payments. The effect tends to be larger for larger spans of control and at higher hierarchical levels but is reversed at the lowest levels.